Vattimo and Ecclesiology. (28th February 2017) - Edward Harris, Matthew
Abstract : Gianni Vattimo (b. 1936) is a postmodern philosopher working within the field of hermeneutics. For someone who is not a theologian first and foremost and who only views himself as a 'half‐believer', it is perhaps hard to see what he could possibly have to contribute to a debate on ecclesiology, a theoretical study of the Church. Nevertheless, his relatively recent writings which constitute his 'return to religion' offer a surprising amount of interesting and relevant material on this topic. On one level, coming from a Catholic background, Vattimo can appear polemical against what he sees as the worst abuses of the Church. However, he grounds this explicitly political and ethical attack in something approximating religionless Christianity. In my opinion, Vattimo's version of religionless Christianity has benefits over Dietrich Bonhoeffer's, not only in embedding the power of Christianity culturally, but also in explaining why the notion of the Church must continue. Nevertheless, a closer analysis shows that his return to religion is centred not on faith or ethics, but too much on hermeneutics and his personal views to be a plausible ecclesiology.